Research in an 'impact culture' - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
workshop on Impact Assessment of Agricultural Research in Eastern and Central Africa, organised by ECART, ASARECA, and CTA November 1999 in Entebbe, Uganda